Sexual Deviations in the LGBT Community on Islamic Law Perspective and Its Impact on the Existence of Muslim Families - Karimullah, Suud Sarim (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2023)
The phenomenon of sexual deviance committed by the LGBT community amid social life is currently attracting attention for researchers to study more comprehensively by conducting a study of LGBT from the perspective of Islamic law and also looking at its impact on the existence of Muslim families because of their understanding and ability to understand the LGBT phenomenon very important. This research is included in the literature review category, complemented by using qualitative methods with a descriptive-analytical approach. Therefore, the results of this study state that LGBT behaviour is not natural or formed by a socio-cultural process at the beginning of human creation. In the implementation of punishment from the perspective of Islamic law, the LGBT community can prevent it from happening again and will create legal awareness for other members of society to avoid this act or other sexual deviations because apart from having an impact on health, it also affects social life, politics, economically, sociologically, psychologically and even religiously have damaged the joints of the family institution. Nonetheless, the existence of the LGBT community must still be respected on a humanitarian basis and given access to education, politics, the economy, and in all other fields.